Water Insecurity in Ontario First Nations: An Exploratory Study on Past Interventions and the Need for Indigenous Water Governance - Rachel Arsenault (Water, 2021)
In 2018, I began an exploratory study involving fourteen Ontario First Nation participants that examined some First Nation water security challenges and opportunities. In acknowledgment that many of the government assessments, reports, and investments to date have failed, this study aims to determine the causes of the water crisis as well as potential solutions by sharing Indigenous perspectives and recommendations on water governance and security. During the study, Indigenous participants were asked interview questions regarding their water and wastewater systems, their historical and current water security conditions, and if they had recommendations for achieving water security in First Nations. The analysis from these interviews demonstrated that there were ten different themes for water security and insecurity in First Nation communities as well as a set of four recommendations shared by the fourteen participants. The participant recommendations are: (1) that Traditional Knowledge (TK) and Indigenous laws be included in water security initiatives and water governance; (2) that provincial and federal governments work with Indigenous communities on their water security challenges and opportunities; (3) that First Nation leadership develops and implements community water protection plans; (4) that Indigenous communities establish an oversight committee or body for monitoring tourist ventures and extractive development projects such as mining on their territories. This paper will also discuss how an Indigenous research paradigm can be applied during the research process to ensure that the information is captured from the Indigenous perspectives of the participants.